Pengaruh Kualitas Produk, Harga dan Keragaman Produk Terhadap Keputusan Pembelian di Maneko Digital - Wahyuningtyas, Yunita Fitri; Fitriyani, Nur (Kajian Ekonomi dan Bisnis, 2020)
This study aims to determine whether product quality, price and product diversity influence either partially or simultaneously on purchasing decisions. The place used in this research is consumers who make purchases at Maneko Digital. This study used a sample of 95 respondents. The approach method used in this research is a quantitative approach. The technique used is non probability sampling, with a purposive sampling approach that is sampling technique with predetermined criteria. The data analysis technique used is the instrument test, classic assumption test, hypothesis test and multiple linear regression analysis. Partial test results, product quality has a positive and significant influence on purchasing decisions 0,346 with a significance of 0,000. Price variable has a positive and significant effect on purchasing decisions 0,259 with a significance of 0.005. Product diversity variable has a positive and significant influence on purchasing decisions 0,342 with a significance of 0.000.